Factor Analysis of prepare for retirement quality of personnel of Rajabhat Maha Sarakham University - PhoSing, Phakdi Pho (Journal of MCU Social Science Review, 2016)
This research aimed to study level of preparation for retirement quality, toanalyze the factor of preparation for retirement quality personnel of Rajabhat MahaSarakham University. The sample was 450 personnel-all of academic and clerical-ofRajabhat Maha Sarakham University; they were selected by stratified randomsampling with faculty and kind of personnel. The instrument was the rating scalequestionnaire with 972 of reliability.Findings;1. The preparation for retirement quality, to analyze the factor ofpreparation for retirement quality personnel of Rajabhat Maha Sarakham Universityas overall was at high level (Mean=3.85), considering each aspect was high level aswell; the mental preparation (Mean= 3.99), the residence preparation (Mean=3.85),the economy preparation (Mean=3.82), the health preparation (Mean=3.82), thetime spending preparation (Mean= 3.75) respectively. Considering each gender werethat;1.1 The preparation for retirement quality of male as overall was at high level, considering each aspect were; 1) the health preparation (Mean=-3.82), 1)the mental preparation (Mean=4.02), 3) the economy preparation (Mean=-3.84), 4)the time spending preparation (Mean=3.83),5) the residence preparation(Mean=3.83).1,2 The preparation for retirement quality of female as overall was athigh level, considering each aspect were; 1) the health preparation (Mean=3.82), 2)the mental preparation (Mean= 3.98), 3) the economy preparation (Mean=3.80), 4)the time spending preparation (Mean=3.70),5) the residence preparation(Mean=3.86).2. The factor of preparation for retirement quality personnel has 35indicators, the values weight of element between 0.545- 0.823, the cumulativepercentage was 63.032 by statistical significant at .05 levels. The 5 importantelements were; the time spending, the economy, the health, the mental , and theresidence respectively.3. The Confirmatory Factor of preparation for retirement quality personnelhad 5 elements and 35 indicators; values weight of element (B) between 0.45- 0.76by statistical significant at .05 levels.To verified consonance of the model of prepare for retirement qualitypersonnel found that the chi-square (x )= 390.78, df =366, p-value= 0.178,GFI=0.95, AGFI=0.91, CFI=1.00, SRMR= 0.028 and RMSEA=0.013. These mean thatthe preparation Models for retirement consonance with the empirical data goodlevel.